Best evidence summary for self-management of radiodermatitis in head and neck cancer patients: an integrative review - Cheng, Lianfang; Zhang, Mingqi; Zheng, Yicen; Lin, Liyu; Xiao, Tingting; Zhang, Man; Huang, Meiling; Xu, Lichun (Frontiers in Oncology, 2025)
AimTo evaluate and synthesize the best evidence for radiodermatitis self-management in head and neck cancer (HNC) patients, and to provide evidence-based guidance for improving their self-management capabilities.Designintegrative review.Data SourcesWe conducted a comprehensive search across integrated English and Chinese databases, relevant guideline networks, and official association websites. The search period was from January 1, 2000, to August 31, 2024, identifying literature on self-managing radiotherapy-induced dermatitis in HNC patients.Review MethodsStudies were screened for eligibility based on the inclusion criteria, such as relevance to the self-management of radiation dermatitis in HNC patients.The methodological quality of the included studies was then independently assessed by two reviewers using established appraisal tools specific to each study design to ensure the inclusion of high-quality evidence.ResultsA total of 21 documents were ultimately included, comprising 7 guidelines, 6 expert consensuses, 2 evidence summaries, 2 recommended practices, 2 clinical decisions, and 2 systematic reviews. These sources yielded 56 pieces of evidence, summarized across six key aspects: learning related knowledge, daily life management, self-monitoring, symptom management, dietary management, and psychosocial support.ConclusionThis study provides a comprehensive summary of the best evidence for radiodermatitis self-management in HNC patients. This compilation can serve as a valuable reference for healthcare professionals guiding patient self-management, thereby facilitating a more scientific and effective approach to patient self-care.ImpactThis review underscores that promoting self-management of radiation dermatitis in HNC patients is crucial for fostering active patient participation in recovery, which may ultimately enhance adherence and improve long-term outcomes.